AI Chatbot Use and Emotional Regulation among Generation Z: A Uses and Gratifications Perspective (Open Society Conference, 2025)
AI chatbots have emerged as a new medium of dynamic interaction among Generation Z, offering a sense of presence, intimacy, security, comfort, and rapid responses in meeting users’ needs, and are frequently utilized for emotional regulation. However, users are often unaware of their underlying needs and motives for engaging with AI chatbot media. This study aims to examine the selection of chatbot media through the lens of the Uses and Gratifications Theory, focusing on individual needs, motivation, interaction, and satisfaction in regulating emotions. The framework is further supported by Interpersonal Emotion Regulation (IER), encompassing indicators such as Interpersonal Acceptance, Interpersonal Reappraisal, Interpersonal Advice, Interpersonal Distraction, Interpersonal Suppression, and Interpersonal Ignorance, which assess emotional regulation in relation to acknowledging and releasing emotions, problem-solving, and seeking advice. A quantitative approach employing a survey method was adopted, targeting Generation Z in Tulungagung, a region that records an annual increase of approximately 3,000 non-permanent residents. The study seeks to identify the relationship between chatbot usage patterns and emotional regulation.